State regulation and the development stages of the health care system in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The work holds the historical and legal analysis of the healthcare system in Kazakhstan, as well as the current problems and prospects for its further improvements. Revealed new vectors of reforming the scope of medical services. There is made an analysis of regulations on this field of study, and the actions of public authorities undertaken to implement the goals and objectives.Key words: healthcare, medicine, medical services, state regulations on the healthcare system, social services of state.